The Cambridge introduction to Russian poetry - Wachtel, Michael (Cambridge University, 2013)
The Cambridge introduction to Russian Poetry presents the major themes, forms, genres, and styles of Russian poetry. Using examples from Russia's greatest poets, Michael Wachtel draws on three centuries of verse, from the beginnings of secular literature in the eighteenth century up to the present day. This book is designed to give readers with even a minimal knowledge of the Russian language an appreciation of Russian poetry. It will be an invaluable tool for students and teachers alike.